Effect of Simvastatin on Cisplatin-induced Nephrotoxicity in Male Rats: Prevention of cisplatin-induced nephrotoxicity - Mohammad Javad Khoshnoud; Baligh Naji Abdeh Moghbel; Hossein Niknahad; Bita Geramizadeh (Iranian Journal of Pharmaceutical Sciences, 2011)
Statins have antioxidant and anti-inflammatory effects that are not directly related to their cholesterol-lowering activity. This study aimed to investigate the effect of simvastatin on the extent of tissue damage in cisplatin-induced nephrotoxicity. Simvastatin was orally given to rats in different doses (1, 2 and 4 mg/kg), 1 h prior to cisplatin injection (5 mg/kg, i.p.). All animals were decapitated 5 days after cisplatin administration. Blood urea nitrogen, creatinine, K and Na levels were measured. The kidney samples used for the measurement of malondialdehyde and glutathione levels or were processed for histopathological studies. Simvastatin at 1 mg/kg caused a significant decrease in serum Na and a significant increase in serum K. Simvastatin at 2 mg/kg significantly increased serum Na, and at 4 mg/kg significantly prevented decrease of GSH levels by cisplatin and significantly decreased serum Na levels. The morphological changes induced by cisplatin treatment were prevented only by 4 mg/kg dose of simvastatin. Thus, simvastatin at 4 mg/kg dose is beneficial in cisplatin-induced nephrotoxicity in rats via prevention of lipid peroxidation, inflammation and endothelial function impairment.